1992
DOI: 10.1007/bf00686402
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitivity of human MCF-7 breast cancer cells to diastereoisomeric diaqua(1,2-diphenylethylenediamine) platinum(II) sulfates and specific platinum accumulation

Abstract: Summary. Cisplatin, raceme-diaqua[1,2-bis(4-fluorophenyl)ethylenediamine]platinum(II) sulfate (compound I), meso-diaqua[ 1,2-bis(4-fluorophenyl)ethylenediamine]-platinum(II) sulfate (compound II), and meso-diaqua[1,2-bis(2,6-dichloro-4-hydroxyphenyl)ethylenediamine]platinum(II) sulfate (compound III) were compared with regard to their effect on the MCF-7 breast cancer cell line in vitro. At equimolar concentrations (5 gM), cisplatin, compound I, and compound II were equiactive after 231 h drug exposure, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…The carrier function of the 1,2-bis(4-fluorophenyl)ethylenediamine ligand has been described on the example of the sulfatoplatinum(II) complexes (meso-and rac-4F-PtSO 4 ), the racemate of which is enriched in the MCF-7 breast cancer cells and binds to DNA to a markedly greater extent than the meso-form and cisplatin [10] . These differences in the uptake kinetics of the diastereomers find their expression in the stronger anti-breast cancer potency of the racemate.…”
Section: Activity Towards the Human Mcf-7 Breast Cancer Cell Linementioning
confidence: 99%
“…The carrier function of the 1,2-bis(4-fluorophenyl)ethylenediamine ligand has been described on the example of the sulfatoplatinum(II) complexes (meso-and rac-4F-PtSO 4 ), the racemate of which is enriched in the MCF-7 breast cancer cells and binds to DNA to a markedly greater extent than the meso-form and cisplatin [10] . These differences in the uptake kinetics of the diastereomers find their expression in the stronger anti-breast cancer potency of the racemate.…”
Section: Activity Towards the Human Mcf-7 Breast Cancer Cell Linementioning
confidence: 99%
“…For triggering maximum inhibitory effects, a dcc of 12 h is sufficient. However, the full impact on the tumor cell proliferation cannot be observed prior to about 175 h after the start of the experiment [10].The studies confirmed that in accordance with its poor effect in MCF-7 breast cancer cell cultures meso-3-PtLLЈ was not enriched in the tumor cells (Table 4: C Pt,c = 3; f < 1).To gain more insight into the influence of the ring substituents in meso-3-PtLLЈ on its absorption by breast cancer cells, we included meso-1-PtLLЈ and meso-2-PtLLЈ in our study. The two [1,2-diarylethylenediamine]-platinum(II) complexes, meso-1-PtLLЈ and meso-2-PtLLЈ, are substituted by either one OH group in each 3-position or by two F atoms in both 2,6-positions (formula see Table 1).…”
mentioning
confidence: 93%
“…In these studies, the 4-fluoro derivative (meso-4-PtSO 4 ) was also included for comparison, since it is structurally related to meso-3-PtSO 4 and, in contrast to the latter, it possesses an inhibitory activity on the human MCF-7 breast cancer cell line comparable to that of cDDP [10]. As in vivo the aquasulfatoplatinum(II) complexes (meso-3-PtSO 4 and meso-4-PtSO 4 ) are quickly transformed into their dichloroplatinum(II) derivatives in vitro due to a surplus of chloride ions (145 mM; [24]).…”
mentioning
confidence: 99%
“…The monosubstituted meso configurated complexes were less active than their diastereoisomers. AAS measurements [4] revealed that mutagenicity corre lates positively with the extent of DNA platination in S. thyphimurium, whereas antitumour activity cannot be explained by the number of DNA platinum adducts [5]. These results suggest that this discrepancy between antitumour activity and mutagenicity are either caused by qualitative than quantitative DNA-platinum adducts or by mechanisms different from DNA cross-link formation.…”
Section: (Iso) Flavonoidsmentioning
confidence: 70%